Differences in hearing levels between siblings with hearing loss caused by GJB2 mutations. Issue 6 (December 2020) - Fujioka, Masato; Hosoya, Makoto; Nara, Kiyomitsu; Morimoto, Noriko; Sakamoto, Hirokazu; Otsu, Masahide; Nakano, Atsuko; Arimoto, Yukiko; Masuda, Sawako; Sugiuchi, Tomoko; Masuda, Shin; Morita, Noriko; et al.
Abstract: Objective: Hearing loss caused by GJB2 mutations is inherited in an autosomal recessive manner (DFNB1); thus siblings of an affected child have a 25% chance of also being affected. Hearing loss among subsequent siblings carrying the same GJB2 mutation is a concern for parents and a frequent topic of enquiry during genetic counseling. Evidence exists for genotype-phenotype correlations of GJB2 mutations; however, no analysis of differences in hearing among siblings, in whom the common genetic background may decrease variation, has been reported. The purpose of the present study was to investigate hearing differences between siblings with identical GJB2 mutations. Methods: We examined the hearing levels of 12 pairs of siblings; each pair had the same pathogenic GJB2 mutations. Differences in hearing acuity between sibling pairs detected by auditory evaluation. Results: No significant correlation was detected between the average hearing levels of first and second affected siblings. Average differences in acoustic threshold >30 dB were observed between four pairs of siblings, whereas the remaining eight pairs had average threshold values within 20 dB of one another. Conclusion: Our results indicate that auditory acuity would be expected to approximate that found in the first child in approximately 70% of subsequent children with GJB2 -mediated hearing loss, whereas 30% of subsequent siblings would have average differences of >30 dB.